Potential impact of filter-feeding invaders on temperate inland freshwater environments - Darrigran, Gustavo Alberto (2002)
Since the 1990s, biological invasions have captured the attention of the scientific community as an important element of global change and a major threat to biodiversity. The inland waters of South America provide two examples of biological invasions. This review examines bivalve invasions in South America, summarizes the research results for two species, the Asian clam (Corbicula fluminea) and the golden mussel (Limnoperna fortunei), and suggests further studies. The rapid expansion of invasive bivalves into these environments involves significant changes. Until now, C. fluminea, the Asian clam, did not produce generalized macrofouling in the Neotropical region, as is common in the Holarctic region. However, the first specific cases of macrofouling by C. fluminea were recently detected in heat interchangers of power stations in Brazil. On the other hand, L. fortunei is provoking new economic impacts in South American freshwaters through macrofouling. Before the invasion by the golden mussel, macrofouling was recorded only in the marine and estuarine environments of the Neotropical region. The impact caused by invasive bivalves in this region is not only economic, however. Rapid changes in the benthic community, favoring the presence of Oligochaeta and Hirudinea, as well as the displacement of native species of mollusks, are among the problems related to the presence of the golden mussel. Another issue is the settlement of golden mussels on native bivalves. This bivalve is now a new element in the diet of some native fish species, being the main food item in some cases.